2015
DOI: 10.1044/2015_jslhr-l-14-0187
|View full text |Cite
|
Sign up to set email alerts
|

What Our Hands Say: Exploring Gesture Use in Subgroups of Children With Language Delay

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractPurpose: The aim of this study was to investigate whether children with receptive-expressive and expressive-only language delay differ in their use of gesture; to examine relationships between their use of gesture, symbolic comprehension and language; and to consider implications for the nature of problems underlying different profiles of early language delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In this paper we report on a follow-up of children with language delay two years after their initial clinical identification at 2-3 years with receptive/expressive (R/ELD) or expressive-only language delay (ELD). Our first study (O'Neill & Chiat, 2015) found performance on two measures of nonverbal sociocognitive skills, gesture use and symbolic comprehension, were significantly associated with receptive but not expressive language, with the R/ELD group scoring significantly below the ELD group on both. These findings supported interactionist theories proposing that new language forms build on social, motor and cognitive precursors, (Ambridge & Lieven, 2011), and were in line with evidence supporting such theories.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In this paper we report on a follow-up of children with language delay two years after their initial clinical identification at 2-3 years with receptive/expressive (R/ELD) or expressive-only language delay (ELD). Our first study (O'Neill & Chiat, 2015) found performance on two measures of nonverbal sociocognitive skills, gesture use and symbolic comprehension, were significantly associated with receptive but not expressive language, with the R/ELD group scoring significantly below the ELD group on both. These findings supported interactionist theories proposing that new language forms build on social, motor and cognitive precursors, (Ambridge & Lieven, 2011), and were in line with evidence supporting such theories.…”
mentioning
confidence: 81%
“…Turning to clinical evidence, in children with Autism Spectrum Disorder (ASD), Ozcaliskan, Adamson and Dimitrova, (2016) found that deictic gesture at 30 months predicted vocabulary development a year later, and Yoder, Watson and Lambert (2015), that the use of intentional communication acts including non-conventional and conventional gestures, measured at 12-16 months, was related to receptive and expressive language growth at 2-4 years. Likewise, cross-sectional studies of children with language delay have reported significant correlations between gesture and profiles of receptive and expressive language (O'Neill & Chiat, 2015;Thal, Tobias, & Morrison, 1991;Thal & Tobias, 1992;Thal & Tobias, 1994), with different uses of gesture sequences and single gesture types related to single word production versus comprehension across a series of studies by Thal and colleagues (Thal, Marchman, & Tomblin, 2013).…”
Section: Gesture Use and Language Developmentmentioning
confidence: 98%
“…In typical development, significant longitudinal relations have been observed between gesture use and receptive (Watt et al 2006, Rowe et al 2008 as well as spoken (Iverson et al 2008) language. In comparison, cross-sectional and longitudinal studies of toddlers with receptive and expressive language delay, primary delays in expressive language (i.e., later talkers), and Down syndrome have found that receptive (but not expressive) language ability was positively correlated with gesture use (e.g., O'Neill and Chiat 2015, Thal et al 1991, Zampini and D'Odorico 2009 In ASD, early gesture use has been shown to be associated with both expressive and receptive language (e.g., Dimitrova et al 2016, Luyster et al 2008, Ozcaliskan et al 2015, above and beyond nonverbal cognition (Charman et al 2003). However, receptive language has been found to be more closely associated with gestures than expressive language in at least one study (Luyster et al 2007a).…”
Section: Relationship Between Gesture and Languagementioning
confidence: 99%
“…) language. In comparison, cross‐sectional and longitudinal studies of toddlers with receptive and expressive language delay, primary delays in expressive language (i.e., later talkers), and Down syndrome have found that receptive (but not expressive) language ability was positively correlated with gesture use (e.g., O'Neill and Chiat , Thal et al . , Zampini and D'Odorico ).…”
Section: Introductionmentioning
confidence: 99%
“…For children with LD, Bello et al (2018) found that conspicuously more of them do not produce declarative pointing gestures compared to TD children. Beyond that, O'Neill andChiat (2015) andO'Neill et al (2019) showed that children with a receptive-expressive LD score more poorly in gesture production tasks than children with an expressive-only LD and that the performance in the gesture tasks in turn predicts later language skills. In earlier publications concerning the sample presented here, we found that children who do not point with the extended index finger at 12 months are at higher risk for LD at 2;0 compared to children who do produce index-finger points at 12 months of age (Lüke et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%